BIMBINGAN TEKNIS PEMBUATAN PUPUK BOKASHI UNTUK PKK RT 01/RW 01 POHJENTREK – PASURUAN - Abdul Chalim; Achmad Chumaidi; Shabrina Adani Putri; Andi Nina (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
Trainings for developing work skills for PKK women in RT 01/RW 01 Pohjentrek Pasuruan are rarely held, so through this PkM activity, residents of RT 01/RW 01 Pohjentrek Pasuruan have been given skills training to be more independent so that they have jobs and a decent life. . One of the skills that can be trained is making bogashi fertilizer. Bokashi fertilizer is a fertilizer made with a composting method that can use an aerobic or anaerobic starter to compost organic matter. This organic material itself can be obtained from household kitchen waste such as leftover vegetables, fruits, rice, etc., so it does not require a fee or tends to be cheap. The PkM was carried out on Friday, October 2, 2020 online as well as team representatives who gave directions and submitted materials for making bokashi fertilizer, video tutorials for making bokashi fertilizer, manuals, composters and bokashi fertilizer products themselves. Publication is carried out on youtube media and the website of the Polynema Chemical Engineering department